Management of chest pain in the French emergency healthcare system: the prospective observational EPIDOULTHO study. (December 2018) - Charpentier, Sandrine; Beaune, Sebastien; Joly, Luc Marie; Khoury, Abdo; Duchateau, François-Xavier; Briot, Raphael; Renaud, Bertrand; Ageron, François-Xavier
Abstract : Objective: The aim of this paper was to describe the epidemiology, and diagnostic and therapeutic strategies that emergency physicians use to manage patients presenting with chest pain at all three levels of the French emergency medical system – that is, dispatch centres (SAMUs: the medical emergency system), which operate the mobile intensive care units (MICUs), and hospitals' emergency departments (EDs), with a focus on acute coronary syndrome (ACS). Patients and methods: All patients with chest pain who contacted a SAMU and/or were managed by a MICU and/or were admitted into an ED were included in a 1-day multicentre prospective study carried out in January 2013. Data on diagnostic and therapeutic management and disposition were collected. An in-hospital follow-up was performed. Results: In total, 1339 patients were included: 537 from SAMU, 187 attended by a MICU and 615 in EDs. Diagnosing ACS was the main diagnostic strategy of the French emergency care system, diagnosed in 16% of SAMU patients, 25% of MICU patients and 10% of ED patients. Among patients calling the SAMU, 76 (14%) received only medical advice, 15 (8%) patients remained at home after being seen by a MICU and 454 (74%) were discharged from an ED. Conclusion: Management of chest pain at the three levels of the French medical emergency system is mainly oriented towards ruling out ACS. The strategy of diagnostic management is based on minimizing missed diagnoses of ACS. Abstract : Supplemental Digital Content is available in the text.